Pengalaman Perempuan Driver Ojek Online dalam Menghadapi Praktik Misoginis di Ruang Publik: Studi Kasus di Suatu Perkumpulan Ojek Online di Jakarta Timur - Hisyam, Ciek Julyati; Seruni, Mayang Puti; Nuraini, Alya Alifah; Islamiya, Fahria Izzatul; Koputri, Keisa; Fauziah, Sipah; Kartika, Sri Yulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation in the transportation sector provides new opportunities for women to work as online ojek drivers. However, their presence in public space exposes their vulnerability to misogynistic practices rooted in patriarchal culture. This study aims to examine the forms of misogynistic practices experienced by female online ojek drivers, as well as understand their strategies in dealing with the situation through the perspective of radical feminism. Using descriptive qualitative method, data was collected through in-depth interviews with female online ojek drivers in East Jakarta. The results showed that they often experience verbal and non-verbal harassment, gender stereotyping, and symbolic marginalization in public spaces. The strategies developed include subtle rejection, utilization of digital security features, community solidarity, and self-image management as a form of resistance to unequal power relations. The findings confirm that public space is not yet fully safe for women, and their struggle reflects a form of resistance to the patriarchal system that still dominates Indonesia’s social order.